KAJIAN PEMANFAATAN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN UMKM DI KOTA KENDARI - Munawir Makmur; Candra Puspita Ningtyas; La Ode Agus Said; Rosikah (Halu Oleo University, 2024)
The purpose of this study is to determine and analyze the impact of the use of Digital Marketing on increasing sales of micro, small and medium enterprises (MSMEs) in Kendari City. The method used in this study is a descriptive research method (single variable data analysis). After the data is collected, the data is grouped numerically, processed using a frequency table, and supplemented with a description of additional information related to the challenges faced by MSMEs in Kendari City. The criteria are MSMEs that use Digital Marketing > 1 year and MSMEs that specifically sell food and clothing. The results of the study show that the use of digital marketing in increasing MSME sales in Kendari City shows that digital marketing strategies have a significant impact on MSME sales growth. The indicators used, namely transaction costs, interactivity, incentive programs, and website design, make an important contribution to creating a positive user experience and encouraging increased sales.